Association Between Birth Weight and Other Factors with the Intelligence Quotient (IQ) of the Student of SMP Negeri 200 Jakarta in 2013 - Abadini, K; Pujonarti, S A (KnE Life Sciences, 2019)
This study aimed to identify the association between birth weight and other factors with the intelligence quotient (IQ) of the student of SMP Negeri 200 Jakarta. The observed sample in this study was the 7th grader consisting of 131 students. The collected data were IQ score, birth weight, HAZ, energy intake, protein intake, iron intake, mother’s education level, and parent’s income. These data collected by using a self-administered questionnaire, 2x24 hours recall interview, and height measurement. The result of this study showed that there was a significant correlation between birth weight, mother’s education level, parent’s income, and IQ (p< 0.05). Keywords: intelligence quotient, IQ, birth weight, mother’s education level, parent’s income